Applying NFV/SDN to DDoS mitigating - Zhang, Man (2018)
Distributed Denial of Service (DDoS) attack has become one of the major threat to current Internet. The attacker firstly gains the control of a large number of hosts. Then by controlling these hosts to send illegal packets to the victim simultaneously, the attacker can easily exhaust the bandwidth or computing resource of the victim. DDoS attack mitigating approaches that apply pre-established defending strategy, functionality or capacity, and guard at fixed locations are costly and not effective. Software Defined Network (SDN) is a new network architecture in which the data plane and the control plane are decoupled. In SDN, the data forwarding function is achieved by using general devices while the control function is implemented by software. Network Function Virtualization (NFV) supports the flexibility in on-demand function instantiation and allocation, and recently finds its applications in handling DDoS attacks. In this dissertation, NFV/SDN is applied into DDoS mitigation. In the framework, network traffic is monitored and analyzed utilizing the SDN features of central control and global network view, and the detection of anomaly traffic will trigger the actions of SDN controller. In this dissertaion we build up an SND environment and demonstrate a DDoS attack on a network topology. By doing simulation experiment, see how we can mitigate it using SDN in real-time. It is shown that the SDN controller can identify the DDoS attackers and disconnect them from the network to prevent any further damages to the network.